Induction of Bax-dependent Neuronal Apoptosis by Amyloid-β Protein Precursor AβPP requires its Localization to Functional Mitochondria. Issue 2 (2017) - Marquardt, Kristin L; Wilkins, Heather M; Manning, Evan; Ignowski, Elizabeth; Mazzarino, Randall; Patterson, David
No abstract available